Promoción comunicacional del humedal abras de mantequilla como potencial del Ecuador - Cosme Maticurema, Luis Alfredo (2021)
To carry out the communicational promotion of the Abras de Mantequilla Wetland, communication is a key tool to publicize the natural resources that the place has such as its biodiversity in flora and fauna, its natural water mirror, unique species that are in danger of extinction and gastronomic wealth, that is why advertising should be used as an instrument to spread the wealth of the place. "Tourism communication aims to achieve a certain attitude or reaction, or to motivate a certain behavior in the recipients through arguments and evaluations that support a given position" (González, 2016). For effective communication to take place, it must adapt to new consumer trends immersed in the world of new technologies, as well as the internet. This is how advertising appears in the media, social networks, web pages and other unconventional advertising. When thinking about a global market, this case study, through the collection of information, shows that the communicational promotion to spread the Abras de Mantequilla Wetland makes notable use of social networks such as Facebook, being able to further enhance the use of communication media conventional and unconventional as well as developing applications for IPhone and Smartphones or direct contact channels by the user in real time. This case study is important to carry out the communicational promotion of the Abras de Mantequilla Wetland as a potential of the equator, making known the natural resources that it has, such as its biodiversity in flora and fauna.